Automated T2* measurements using supplementary field mapping to assess cardiac iron content. Issue 2 (4th January 2013) - Taylor, Brian A.; Loeffler, Ralf B.; Song, Ruitian; McCarville, Mary E.; Hankins, Jane S.; Hillenbrand, Claudia M.
<x xml:space="preserve">Abstract</x> Purpose To develop and evaluate an algorithm that automatically identifies high‐susceptibility areas and excludes them from T2* measurements in the left ventricle (LV) for myocardial iron measurements. Materials and Methods An autoregressive moving average (ARMA) model was implemented on multigradient echo scans of 24 patients (age range 3–45 years, 10 male/14 female). Voxels with relatively high susceptibility (>3 Hz/mm) were flagged and deselected from the T2* calculations for iron quantification. The mean, standard deviation, and coefficient of variation (CoV) of the ARMA‐defined region were compared to the CoV of four distinct regions of the LV and the entire LV using a Student's t‐test (α = 0.05). Results The CoV of T2* values obtained by the ARMA method are comparable with that in the interventricular septum (IS), where susceptibility was the lowest (CoV = 0.31). The ARMA method provides a greater area (51.9 ± 13.7% of the LV) to measure T2* than that using the IS alone (21.1 ± 3.4%, P < 0.0001). Areas where low susceptibility are measured corroborate with areas reported in previous studies that investigated T2* variations throughout the LV. Conclusion An automated method to measure T2* relaxation in the LV with minimal effects from susceptibility has been developed. Variability is reduced while covering more regions for cardiac T2* calculation. J. Magn. Reson. Imaging 2013;38:441–447. © 2012 Wiley Periodicals, Inc.